2023
DOI: 10.3390/ani13193140
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Mixed Organic Acids Improves Growth Performance, Immunity, and Antioxidant Capacity and Maintains the Intestinal Barrier of Ira Rabbits

Zhixin Lin,
Guofeng Yang,
Min Zhang
et al.

Abstract: The aim of this study was to investigate the effects of mixed organic acids (MOAs) on growth performance, immunity, antioxidants, intestinal digestion, and barrier function in Ira rabbits. A total of 192 weaned male Ira rabbits at 35 days of age were randomly assigned to four groups with six replicates of eight rabbits each. The rabbits in the control group (CON) were fed a basal diet, and the antibiotic group (SAL) was fed a basal diet supplemented with 60 mg/kg salinomycin. The test groups were fed a basal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Meanwhile, intestinal morphology changes accompany with the alteration of intestinal digestive enzyme activity ( Iji et al, 2001a , b ). Amylase, sucrase, maltase, and lipase are the main enzymes for starch, disaccharide, and lipid digestion, and their activity partly reflect the intestinal digestion and absorption capacity ( Wan et al, 2017 ; Lin et al, 2023 ). In this study, dietary COS supplementation increased jejunal lipase activity, which indicated that COS promoted the maturation of the digestive system and had beneficial effects on lipid digestion in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, intestinal morphology changes accompany with the alteration of intestinal digestive enzyme activity ( Iji et al, 2001a , b ). Amylase, sucrase, maltase, and lipase are the main enzymes for starch, disaccharide, and lipid digestion, and their activity partly reflect the intestinal digestion and absorption capacity ( Wan et al, 2017 ; Lin et al, 2023 ). In this study, dietary COS supplementation increased jejunal lipase activity, which indicated that COS promoted the maturation of the digestive system and had beneficial effects on lipid digestion in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal mucosal immune system comprises lymph nodes, lamina propria, and epithelial cells, which constitute a protective barrier for maintaining intestinal integrity ( 52 ). M cells secrete SIgA through the polymeric immunoglobulin receptor in the crypts, effectively defending against the invasion of pathogens and commensal microorganisms ( 53 , 54 ). As the predominant immunoglobulin in the intestine, Shiga provides immune protection to prevent the penetration of microorganisms and mucosal antigens into the mucosal barrier through immune exclusion ( 55 ).…”
Section: Discussionmentioning
confidence: 99%